PERBANDINGAN KEBOCORAN APIKAL PEMAKAIAN SILER BERBAHAN DASAR KALSIUM HIDROKSIDA DAN RESIN MENGGUNAKAN ALAT PREPARASI PROTAPER MANUAL DAN ROTARI - , FERRA SOFIANA PRIMASANTI; , drg. Triendra Untaru, M.Kes., Sp.KG ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to compare the apical leakage by the use of calcium hydroxide and resin based siler using manual and rotary Protaper. This study uses 16 of the mandibular premolars. Teeth were randomly divided into two groups and the crowndown preparation using this method. The first group performed the root canal preparation using rotary Protaper and the second group using the manual. Group I were divided randomly into 2 groups IA and IB, whereas group II also were randomly divided into IIA and IIB. Each group consists of four teeth, the tooth is filled with gutta-percha with a single cone technique, which distinguishes these two groups, groups IA and IIA performed root canal filling with calcium hydroxide-based Siler Sealapex (Kerr) and group IB and IIB by Siler-based resin TopSeal (Densply). The penetration of 2% methylene blue made by soaking for 48 hours. Apical leakage was measured under a stereo microscope after dental tool is divided into 2 sections (mesial and distal). The results of this study showed that apical leakage in Siler usage-based resins using rotary root canal preparation Protaper smallest visible. The results of statistical calculations using Anova two paths followed by the Tukey test showed an average leakage of significance (p <0.05).